2020
DOI: 10.7759/cureus.8153
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cysticercosis Presenting With Recurrent Epileptic Seizures

Abstract: Cerebral cysticercosis is the most common parasitic disease of the human nervous system. It is endemic to some tropical countries but has rarely been described in Vietnam. We report three cases of neurocysticercosis in patients from northwest Vietnam presenting with recurrent epileptic seizures. Hypereosinophilia and positive immunoglobulin G (IgG) antibodies to cysticercosis were detected in two patients and three patients, respectively. The brain MRI showed multiple ring-enhancing cerebral lesions with a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…Other symptoms mainly were movement disorder, nausea, and vomiting. Most patients presented with epileptic seizures [ 18 , 19 ], but our case did not. A review showed that over 50% of patients with subarachnoid cerebral cysticercosis have imaging evidence of vasculitis [ 20 ].…”
Section: Discussioncontrasting
confidence: 60%
“…Other symptoms mainly were movement disorder, nausea, and vomiting. Most patients presented with epileptic seizures [ 18 , 19 ], but our case did not. A review showed that over 50% of patients with subarachnoid cerebral cysticercosis have imaging evidence of vasculitis [ 20 ].…”
Section: Discussioncontrasting
confidence: 60%